Strategi Komunikasi Pemasaran Pariwisata Dalam Promosi Destinasi Wisata Taman Kincir Marigold Garden Karawang - Iqlima Nursyadiah; Firdaus Yuni Dharta; Rastri Kusumaningrum (Peneliti.net, 2023)
others; advertising, personal selling, sales promotion, and public relations. The research method used is using a qualitative research method with a qualitative descriptive. In the acquisition of data collection is using interviews, observation and documentation. The research results obtained show that the promotion strategy has been successfully implemented optimally even though it has not been maximized in its marketing communication activities. This research shows that the community of tourism marketing communication mix activities carried out by the managements of Taman Kincir Marigold Garden Karawang is able to target tourist visitors in various ways such as: distributing banners in the area around tourist objects, distributing acusing social media platforms, working with media, working with community members, agencies or assistance from the government, working with private institutions and schools, also provide several discounts and discounts to school children, tahfidz, orphanages, or other visitors, then take part in exhibitions (events), update new programs and Another interesting thing is for its tourist education facilities, as well as providing the best service for tourist visitors.